ANALISIS KEBIJAKAN DAN PROGRAM SUBSEKTOR PETERNAKAN KABUPATEN LAMPUNG BARAT - Hotmuda Simarmata; Hardinsyah Hardinsyah; Diah Krisnatuti Pranadji (Food and Nutrition Society of Indonesia, 2008)
This study aims to analyze the policy, program, activity and budgetting of husbandry subsector in West Lampung Regency. The study was conducted retrospectively, studying documents of policy 2003-2007 in Husbandry and Animal Health Agency of West Lampung and interviewing respondents of the officials involved in the drafting of the program, decision makers, and groups of farmers from November to December 2008. Data that were required in this research, consist of primary and secondary data and was analyzed by descriptive analysis, content analysis and SWOT analysis.The results of this research showed that the formulation of policy and program had been in line with the regulation, but there were some constraints in implementing the policy and program in form of activities due to the limited budget. Budgeting allocation portion for the development food resources from husbandry for 4 years was higher than supporting activities, except in the fifth year. Implementation of husbandry sub-sector, especially cattle breeding was enthusiastically welcomed by the community indicated by their high motivation and initiatives. The environment has changed from the previous period so that the future concept will focus on the breeder empowerment and capital access and strategy by intensifying animal breeding culture, building husbandry centers and partnership with private sectors.